Gambaran Visum et Repertum (VeR) Perlukaan di Instalasi Kedokteran Forensik dan Medikolegal RSUD Abdul Wahab Sjahranie Samarinda Tahun 2015-2019: Overview of Visum et Repertum (VeR) of Injuries at the Forensic Medicine and Medicolegal Installation of Abdul Wahab Sjahranie Hospital, Samarinda 2015-2019 - Andre Wijaya; Daniel Umar; Hary Nugroho (Jurnal Sains dan Kesehatan, 2021)
Visum et Repertum (VeR) is a written statement made by a doctor, forensic specialist or other expert in order to bridge the medical and legal aspects. VeR has several types depending on the condition of the victim, including VeR for living victims and VeR for dead victims. Of the various types of VeR, VeR of living victims, especially injury cases, is the most requested. The purpose of this study is to determine the description of victims, such as the age of the victim, sex, type of violence and degree of injury to the victim and the quality of VeR in the Forensic Medical Installation. and Medicolegal Abdul Wahab Sjaranie Regional Hospital, Samarinda in 2015-2019. This research is a retrospective descriptive study, sourced from secondary data in the form of archives of victims of VeR injuries at the Forensic Medicine and Medicolegal Installation of Abdul Wahab Sjaranie Hospital Samarinda in the last 5 years and using purposive sampling method. The research sample was 332 VeR. The data was then processed to describe the description of the victim according to the variables and Herkuntanto scoring was carried out to see the quality of the VeR. Then the results of the VeR of injuries consisting of 81.9% (n = 272) of victims aged over or equal to 18 years were the most among the victims. The majority of victims were male 62.7% (n = 208), the most blunt type of violence was 78% (n = 259) and the most dominant degree of injury 1 or degree of minor injury was 48.8% (n = 162) . The quality of the VeR injury to the introduction, coverage and conclusions is in the good category with a value order of 85%; 96%; and 99.5%. So it was concluded that the quality of the VeR of the injuries at the Forensic Medicine and Medicolegal Installation of the Abdul Wahab Sjaranie Regional Hospital was valued at 97.2%, which means good category.